DeepEmSat: Deep Emulation for Satellite Data Mining - Duffy, Kate; Vandal, Thomas; Li, Shuang; Ganguly, Sangram; Nemani, Ramakrishna; Ganguly, Auroop R. (Frontiers in Big Data, 2019)
The growing volume of Earth science data available from climate simulations and satellite remote sensing offers unprecedented opportunity for scientific insight, while also presenting computational challenges. One potential area of impact is atmospheric correction, where physics-based numerical models retrieve surface reflectance information from top of atmosphere observations, and are too computationally intensive to be run in real time. Machine learning methods have demonstrated potential as fast statistical models for expensive simulations and for extracting credible insights from complex datasets. Here, we develop DeepEmSat: a deep learning emulator approach for atmospheric correction, and offer comparison against physics-based models to support the hypothesis that deep learning can make a contribution to the efficient processing of satellite images.